New endoperoxides highly active in vivo and in vitro against artemisinin-resistant Plasmodium falciparum - Lobo, Lis (2021)
Background: The emergence and spread of Plasmodium falciparum resistance to artemisinin-based combination therapy in Southeast Asia prompted the need to develop new endoperoxide-type drugs. Methods: A chemically diverse library of endoperoxides was designed and synthesized. The compounds were screened for in vitro and in vivo anti-malarial activity using, respectively, the SYBR Green I assay and a mouse model. Ring survival and mature stage survival assays were performed against artemisinin-resistant and artemisinin-sensitive P. falciparum strains. Cytotoxicity was evaluated against mammalian cell lines V79 and HepG2, using the MTT assay. Results: The synthesis and anti-malarial activity of 21 new endoperoxide-derived compounds is reported, where the peroxide pharmacophore is part of a trioxolane (ozonide) or a tetraoxane moiety, flanked by adamantane and a substituted cyclohexyl ring. Eight compounds exhibited sub-micromolar anti-malarial activity (IC50 0.3-71.1 nM), no cross-resistance with artemisinin or quinolone derivatives and negligible cytotoxicity towards mammalian cells. From these, six produced ring stage survival < 1% against the resistant strain IPC5202 and three of them totally suppressed Plasmodium berghei parasitaemia in mice after oral administration. Conclusion: The investigated, trioxolane-tetrazole conjugates LC131 and LC136 emerged as potential anti-malarial candidates; they show negligible toxicity towards mammalian cells, ability to kill intra-erythrocytic asexual stages of artemisinin-resistant P. falciparum and capacity to totally suppress P. berghei parasitaemia in mice.